A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK NEGERI 2 PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Muhammad Arief Budiono; Fakhri Ras; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed at finding out how the ability of the first year students of SMK Negeri 2 Pekanbaru in comprehending Recount texts. The design of the research was one class for try-out test and one class for real test. The population was the first year students of SMK Negeri 2 Pekanbaruin second semester of academic year 2016/2017. The sample was 27 students of class X.1 which were chosen by using cluster random sampling. The data were collected by giving 5 recount texts in form of multiple choices test. From the five texts, there were 30 items which focus on six components, they are finding main idea, factual information, references, meaning of difficult word, restatement, and social function. The results of the study revealed that the mean score of the students’ ability in comprehending recount texts is 57.51. It means that the ability of the first year students of SMK Negeri 2 Pekanbaru in comprehending recount texts was categorized into average level. The highest score obtained by the students was in comprehending main idea with the mean score of 76.29 which was categorized into good level, and the lowest score that the students got was in comprehending restatement, with the mean score of 40.00 which is categorized into poor level. Based on the result of this research, it is suggested that the students to learn more about comprehending recount text, particularly about comprehending restatement.Keywords: Students’Ability, Reading Comprehension, Recount text.